No Stone Left Unturned: Exploring the Convergence of New Capitalism in Inclusive Education in the U.S. - Waitoller, Federico R.; Kozleski, Elizabeth B. (Education Policy Analysis Archives, 2015)
This paper examines how inclusive education reform is appropriated when New Capitalism work practices dominate the discourse of school improvement in an urban school. We asked how New Capitalism mediates the formation of a professional vision for inclusive education. Using analytical tools from Critical Discourse Analysis (CDA), we analyzed school, district, and university documents and artifacts, interviews, field observations gathered by site professors, videos of teachers’ classroom practices, and video-stimulated interviews. The findings demonstrate how New Capitalism shaped a professional vision (Goodwin, 1994) for inclusive education through the deployment of certain technologies such as performativity and its graphic displays of quality and auditing practices. Performativity shaped relationships among school personnel and their understanding of their work, inclusive education, and students from ethnic minorities struggling to learn. Our discussion of the findings and our recommendations are guided by an inclusive education agenda that addresses issues of misdistribution, misrecognition, and misrepresentation.